ANALISIS REALOKASI DAN REFOCUSING ANGGARAN DANA DESA PADA MASA PANDEMI COVID-19 (Studi Kasus pada Kabupaten Kuantan Singingi) - Yohana Rise; Darlis Edfan; Supriono Supriono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine whether the implementation is in accordance with the plan regarding shifting the village fund budget during the COVID-19 pandemic. Changes in regulations regarding the use of village funds in handling COVID-19 in Kuantan Singingi Regency include (1). The use of village funds for the prevention and handling of Covid-19; (2). Village Cash Intensive Work; (3). Village Cash Direct Assistance. To achieve this objective, a qualitative method with the type of case study was used. The population in this study was 218 villages in Kuantan Singingi Regency, then the researchers divided the villages into four regions based on the geographical location of each village, the data on the number of covid prevention budgets in the village were sourced from the Social and Village Empowerment Service (Dissos PMD). Data collection techniques using interview techniques, observation and documentation. To ensure the validity of the data, triangulation was carried out, namely source triangulation and technical triangulation. Informants in this study consisted of key informants, key informants and supporting informants. The key informants were the Head of the Village and Community Empowerment Social Service, the Village Arrangement and Cooperation Section, and the Village Finance Section. Data analysis is done by collecting data, reducing data, and making conclusions. The results showed that the reallocation and refocusing of the Village Fund for the prevention and handling of Covid19 in Kuantan Singingi Regency was Rp. 177,009,214,000,-. Reallocation and Refocusing of Village Funds for Cash Intensive Work 51,808,938,000,-. And Direct Cash Assistance 600 thousand per month within 3 months of distribution. During the Covid-19 pandemic, in the administrative and accountability stages, there were obstacles, namely the implementation of unexpected expenditures, the budget that had been set in the estimated costs that had been budgeted, there were price differences in the market. Another problem is that there is overlapping data or duplicate data in the distribution of the aid.Keyword : Village Fund, Reallocation, Refocusing, Covid-19 Pandemic